Characteristics and formation mechanism of Carbonate buried hill fractured-dissolved reservoirs in Bohai Sea, Bohai Bay basin, China - Huang, Zhi; Yang, Haifeng; Ye, Tao; Deng, Hui; Guo, Jingzhen; Liang, Shuyi; Xiao, Shuguang; Ma, Cunfei (Frontiers in Earth Science, 2023)
Carbonate buried hill madeexploration breakthroughs recently in the offshore Bohai Bay Basin, China, but the plane distribution of the buried hill reservoirs are unclear due to the highly heterogeneous. Taking the CFD2 oilfield as an example, based on core, thin section, seismic, and well logging data, the characteristics of Carbonate buried hill reservoirs in the study area were clarified, the formation mechanism of the reservoirs was discussed, and the development model of the reservoir was established. The results show that the reservoirs are mainly fractured-dissolved reservoirs, and the formation of the reservoirs is mainly related to structural fractures and fluid dissolution along the fractures. The NWW-trending structural fractures were formed under the control of the Indosinian compression, and the NEE-trending structural fractures were formed under the control of the Yanshanian strike-slip transpression. Dolomite is more brittle than limestone and is the main lithology for forming effective fractures. Structural fractures provide favorable channels for atmospheric water dissolution. The C and O isotope values reveal that at least two stages of dissolution have occurred in the study area which are supergene karstification and burial karstification. A model of the fractured-dissolved reservoir under the control of “structure-lithology-fluid” was established. This model highlights that the structural fractures formed by tectonic activities are crucial to reservoir development, and lithology is the internal factor controlling reservoir distribution. Dolomite exhibits the compressive strength of only half of the limestone, and it is the dominant lithology for reservoir development. The dissolution of atmospheric water in the two stages along the fractures greatly improved the physical properties of the reservoirs, and it is the guarantee for the development of effective reservoirs.